The Mining Obligations: The Minimum Production, The Right of Validity, The Penalty and Criticisms to its Regulation - Cuneo Alendez, David (2015)
Mining obligations are a matter of great importance in the Mining Law and even more regarding the owners of mining rights, because the breach of any of these obligations by the leatters will lead mining concessions to extinction.This article develops in the first part the general framework for mining obligations, both those borned as a result of the formulation and granting of a mining concession and the consequences generated because of its breach. In the second part we analyze the problem regarding for the poor regulation of expiration (which is one of the most important causes of extinction of a mining concession) and their most notorious example due to lack of knowledge of timely payment.